The Relationship between Workload and Heat Work Climate with Work Fatigue Incidence in Areca Nut Farmers - Budi Aswin; Rd. Halim (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The causes of work fatigue consist of several conditions, including working climate conditions, especially hot work climates and workloads. This study aims to analyze the workload and hot work climate on the incidence of work fatigue. The study used a cross-sectional design. The research population is all areca nut farmers in Sungai Tawar Village, Mendahara District, Tanjung Jabung Timur Regency. The research sample amounted to 90 people who were taken using proportional strafied random sampling technique. Collecting data by observation, and using a questionnaire. Data processing was carried out univariate and bivariate using chi-square test at 95% confidence interval. The results showed that the workload (p = 0.003) and heatt work climate (p = 0.001) related to the incidence of work fatigue in areca nut farmers. It is recommended that areca nut farmers do stretching movements before work and use personal protective equipment such as hats, long shirts, trousers and boots in order to minimize the incidence of work fatigue.